Medidas de precaução específica direcionadas a acompanhantes e visitantes: visão dos profissionais de Comissão de Controle de Infecção Hospitalar - Estequi, Jeanine Geraldin (Universidade Federal de São Carlos, 2021)
Introduction: Health care-related infections are a global problem. Recently, the implementation of infection prevention programs has been recognized especially in view of the experience with COVID-19 and with resistance to antimicrobials. The number of patients admitted with suspicion or known to be colonized by specific agents of epidemiological importance has shown a significant increase and during their stay in the hospital they may develop a feeling of loneliness and feel vulnerable, thus, the inclusion of companions and permission to visit represents an important positive impact on your recovery. Given the risk of transmissibility of pathogens from the colonized patient, attention is needed to prevent the health of the companion or visitor. However, there are no guidelines that guarantee the creation of recommendations aimed at these people, which may or may not be present in Hospital Infection Control Programs, in addition, the meaning and usefulness of infection prevention measures may not be well understood among health professionals. companions and visitors, generating health risk. The scarcity of productions related to this theme points out weaknesses in relation to the theme. Objective: To relate the recommendations contained in the Hospital Infection Control Programs aimed at companions and visitors of hospitalized patients under specific precautions with the perception of the professionals of the Hospital Infection Control Commission regarding the possible barriers to the implementation of these recommendations and their accession by companions and visitors. Methods: Descriptive and exploratory study, like a Survey, with a quantitative approach, carried out with 89 professionals from Hospital Infection Control Commissions, between March and June 2020. The recruitment of participants took place by “Snowball” sampling and data analyzed according to the frequency of responses. Results: The sample consisted of 67 nurses, 21 doctors and 1 nursing technician. The recommendations contained in the Hospital Infection Control Programs were not uniform, with hand hygiene, not entering other patients' rooms and the use of personal protective equipment prevalent for all types of precautions. Based on the perception of professionals of the Hospital Infection Control Commission, the main barriers were the lack of knowledge of companions and visitors about precautions, the lack of professional guidance and inadequate infrastructure, in addition, non-compliance actions carried out by companions and visitors related to the use of personal protective equipment and entering other rooms, were reported as hindering the process of implementing the recommendations. Conclusion: There was no uniformity in the recommendations contained in the Hospital Infection Control Programs. The study revealed practices that can lead to increased institutional costs, a shortage of health products and the representation of health risks. Professional training and adequate information tools for companions and visitors are points that must be analyzed to strengthen adherence to the recommendations.
Specific precautions directed to companions and visitors: perception of Hospital Infection Control Commission professionals
Keywords: Controle de infecção; Precaução específica; Isolamento de pacientes; Enfermagem; Acompanhantes; Visitantes; Infection control; Specific precaution; Isolation of patients; Nursing; Companion; Visitors; CIENCIAS DA SAUDE::ENFERMAGEM